2018
DOI: 10.1039/c8fo01111g
|View full text |Cite
|
Sign up to set email alerts
|

Troxerutin subdues hepatic tumorigenesisviadisrupting the MDM2–p53 interaction

Abstract: Hepatocellular carcinoma (HCC) is the sixth most common cancer and the third most common cause of mortality worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 48 publications
3
9
0
Order By: Relevance
“…The mast cell count in the duodenal segment of mucositis mice indicated that administration of TRX decreased the number of degranulated and granulated mast cells that were induced by 5-FU treatment. Another study has shown that TRX is capable of reversing mastocytosis [18]. According to Kheirollahi et al [53], flavonoids reverse tissue damage by preventing neutrophil and mast cell degranulation, which corroborates with the findings obtained in this study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The mast cell count in the duodenal segment of mucositis mice indicated that administration of TRX decreased the number of degranulated and granulated mast cells that were induced by 5-FU treatment. Another study has shown that TRX is capable of reversing mastocytosis [18]. According to Kheirollahi et al [53], flavonoids reverse tissue damage by preventing neutrophil and mast cell degranulation, which corroborates with the findings obtained in this study.…”
Section: Discussionsupporting
confidence: 91%
“…As shown by our study, TRX treatment (100 mg/kg) reverses the 5-FU-induced increase of MDA levels and prevents GSH consumption in mice. The antioxidant effect of TRX shown in the present study has also been reported by several published studies in different experimental models [17][18][19]21,[57][58][59][60][61].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Also, it was shown that troxerutin reduces the nuclear translocation of NF-kB (p65 subunit) through LKKB downregulation and consequently, resulting in decreased inflammatory responses, proliferation and cell survival. In another study, the inhibitory effect of troxerutin on hepatic tumorigenesis was evaluated [49]. It was shown that troxerutin diminishes hepatic nodule formation, changes in enzymatic status, frequencies of glutathione-s-transferase and PCNA and marker of S phase progression.…”
Section: Anti-tumor Effectmentioning
confidence: 99%
“…Acetylshikonin can directly promote HepG2 cell apoptosis by activating p53/PUMA/Bax pathway 156 . Troxerutin can subdue hepatic tumorigenesis via disrupting the MDM2-p53 interaction by decreasing the expression of MDM2 and increasing that of wild-type p53 157 .…”
Section: Anti-hcc By Restoring P53 Function and Normalizing Mdm2-p53 mentioning
confidence: 99%